APOE gene variants in primary dyslipidemia. (July 2021) - Khalil, Yara Abou; Rabès, Jean-Pierre; Boileau, Catherine; Varret, Mathilde
Abstract: Apolipoprotein E (apoE) is a major apolipoprotein involved in lipoprotein metabolism. It is a polymorphic protein and different isoforms are associated with variations in lipid and lipoprotein levels and thus cardiovascular risk. The isoform apoE4 is associated with an increase in LDL-cholesterol levels and thus a higher cardiovascular risk compared to apoE3. Whereas, apoE2 is associated with a mild decrease in LDL-cholesterol levels. In the presence of other risk factors, apoE2 homozygotes could develop type III hyperlipoproteinemia (familial dysbetalipoproteinemia or FD), an atherogenic disorder characterized by an accumulation of remnants of triglyceride-rich lipoproteins. Several rare APOE gene variants were reported in different types of dyslipidemias including FD, familial combined hyperlipidemia (FCH), lipoprotein glomerulopathy and bona fide autosomal dominant hypercholesterolemia (ADH). ADH is characterized by elevated LDL-cholesterol levels leading to coronary heart disease, and due to molecular alterations in three main genes: LDLR, APOB and PCSK9 . The identification of the APOE- p.Leu167del variant as the causative molecular element in two different ADH families, paved the way to considering APOE as a candidate gene for ADH. Due to non mendelian interacting factors, common genetic and environmental factors and perhaps epigenetics, clinical presentation of lipid disorders associated with APOE variants often strongly overlap. More studies are needed to determine the spectrum of APOE implication in each of the diseases, notably ADH, in order to improve clinical and genetic diagnosis, prognosis and patient management. The purpose of this review is to comment on these APOE variants and on the molecular and clinical overlaps between dyslipidemias. Graphical abstract: Image 1 Highlights: FH refers to LDLR mutation carriers only while ADH includes all type IIa hyperlipoproteinemias ( LDLR, APOB, APOE, PCSK9 …). Rare APOE variants were reported in different dylipidemias including FD, FCH, lipoprotein glomerulopathy and bona fide ADH. Due to the addition of non Mendelian factors, dyslipidemias associated with APOE variants often strongly overlap. Screening of the APOE gene is warranted in the setting of ADH molecular diagnosis, along with LDLR, APOB, and PCSK9 genes.